Analisis perkembangan penerimaan pajak daerah pada Badan Pendapatan Daerah Kota Manado - Wagania, Stella Lanova; Kalangi, Lintje; Walandouw, Stanley Kho (Riset Akuntansi dan Portofolio Investasi, 2024)
This study aims to analyze the contribution of regional taxes to regional tax revenues at the Manado City Regional Revenue Agency in 2017-2023 and the development of its contribution during 2024-2030. This study also analyzes the factors that influence regional tax revenues at the Manado City Regional Revenue Agency in 2017-2023 and the government’s efforts to maximize regional tax revenues. The data analysis method used is qualitative approach especially case study. The results show that the contribution of the realization of regional taxes of Manado City over 2017-2023 is at the lowest criteria, very poor and the highest criteria is moderate. Restaurant Tax and Street Lighting Tax contribute better than other types of regional tax. The development of the realized contribution of regional tax types of Manado City for 2024-2030 period based on analysis of regional tax revenue data for 2017-2023 is varies, experiencing decreases and increases.